Early embryo morphokinetics is a better predictor of post-ICSI live birth than embryo morphology: Speed is more important than beauty at the cleavage stage - Bartolacci, Alessandro; Dal Canto, Mariabeatrice; Guglielmo, Maria Cristina; Mura, Laura; Brigante, Claudio; Mignini Renzini, Mario; Buratini, Jose [UNESP] (Cambridge University Press (CUP), 2021)
Given the importance of embryo developmental competence assessment in reproductive medicine and biology, the aim of this study was to compare the performance of fertilization and cleavage morphokinetics with embryo morphology to predict post-ICSI live birth. Data from embryos cultured in a time-lapse microscopy (TLM) incubator and with known live birth outcomes (LB: embryos achieving live birth, n = 168; NLB: embryos not achieving live birth, n = 1633) were used to generate receiver operating characteristic (ROC) curves based on morphokinetic or morphological scores, and the respective areas under the curve (AUC) were compared. The association between live birth and 12 combinations of four morphokinetic quality degrees (A-D) with three morphological quality degrees (A-C) was assessed using multivariate analysis. Morphokinetic parameters from tPNa to t8 were reached earlier in LB compared with NLB embryos. The ROC curve analysis indicated that morphokinetic information is more accurate than conventional morphology to predict live birth [AUC = 0.64 (95% CI 0.58-0.70) versus AUC = 0.58 (95% CI 0.51-0.65)]. The multivariate analysis was in line with AUCs, revealing that embryos with poor morphokinetics, independently of their morphology, provide lower live birth rates (P < 0.001). A considerable percentage of embryos with top morphology presented poor morphokinetics (20.10%), accompanied by a severely reduced live birth rate in comparison with embryos with top morphology and morphokinetics (P < 0.001). In conclusion, TLM-derived early morphokinetic parameters were more predictive of live-birth achievement following ICSI than conventional morphology.
Keywords: ICSI; Keywords; Live birth; Morphokinetics; Morphology; Time-lapse microscopy